(untitled) (ARQUISUR Revista, 2017)
The possibility for buildings to create a part of the energy they consume, means a paradigm shift. One of the characteristics of solar photovoltaics is its ability to integrate into the building envelope protecting from excess solar gain and generating energy at the same time, restoring the connection between the built and the flows of nature, even partially. This article deals with cases of works of different scales with solar architectural integration, from valuation analytical matrices in which interrelates categories forms, uses and meanings with the variable practicability, spatiality, materiality and habitability.